The Influence of Influencer Marketing Content on the TikTok Platform on Consumer Buying Interest (Case Study of Labubu Blind Box Products at Popmart, Bandung City in 2026) - Diva Aulia; Leni Cahyani; Laksmi Saraswati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research discusses the influence of content marketing and influencer marketing on the TikTok platform on consumer buying interest in Blind Box Labubu products at Pop Mart Bandung City. This research is motivated by the increasing use of TikTok as a digital promotional medium, especially in introducing popular products such as Labubu. The aim of this research is to find out how much influence marketing content and influencer marketing have on consumer buying interest. The method used is a quantitative approach with explanatory research. Data was collected through an online questionnaire using Google Forms to 110 respondents who were active TikTok users, lived in Bandung City, and had an interest in Blind Box Labubu products. The sampling technique used purposive sampling, while data analysis was carried out with the help of SPSS 25 through validity, reliability, classical assumptions, multiple linear regression, t test, F test, and coefficient of determination. The research results show that content marketing and influencer marketing have a positive and significant effect on consumer buying interest. Influencer marketing has a stronger influence than content marketing. Together, these two variables are able to explain 53.6% of the variation in consumer buying interest. Thus, marketing strategies through TikTok content and influencers can be an effective way to increase consumer buying interest in Blind Box Labubu products.